Inotrope Use and the Risk of Intraventricular Hemorrhage in Preterm Neonates: A Systematic Review and Meta Analysis - Anggita Dian Karera; Delta Iswara; Amanah Sekar Kinasih; Dyah Ati Sayuka; Din Alfina (CV. AFDIFAL MAJU BERKAH, 2025)
More than 40% of neonatal hypotension cases are managed with inotropes; however, recent evidence indicates that inotrope administration, rather than hypotension itself, is independently associated with an increased risk of intraventricular hemorrhage (IVH) after adjustment for confounding factors. This systematic review and meta-analysis aimed to evaluate the association between inotrope use and the occurrence of IVH among preterm neonates. The study followed PRISMA guidelines. A systematic literature search was conducted through PubMed, Scopus, ScienceDirect, and Google Scholar. The methodological quality of each study was assessed using the Newcastle-Ottawa Scale (NOS) for case-control and cohort designs. Relevant data were extracted for qualitative and quantitative synthesis. Meta-analysis was performed using a random-effects model based on adjusted odds ratios (aORs) reported in each study, and the results were presented as pooled aORs with 95% confidence intervals. Eight studies met the inclusion criteria. The meta-analysis showed that inotrope use was significantly associated with a higher risk of IVH in preterm neonates, including IVH of any grade (pooled OR 2.03, 95% CI 1.25-3.29) and severe IVH (pooled OR 2.00, 95% CI 1.33-3.02). Overall, inotrope use doubled the risk of IVH (pooled OR 2.00, 95% CI 1.48-2.70). These findings emphasize the need for cautious and strictly indicated inotrope administration along with standardized hemodynamic management.